Notes on the caddisfly fauna of Lake Matano in Central Sulawesi (Insecta, Trichoptera). - Mey, Wolfram (Contributions to Entomology = Beiträge zur Entomologie, 2006)
Samples of the Trichoptera fauna of Lake Matano in Central Sulawesi contained a total of 14 species. Ten species proved to be unknown and are described as: Agapetus tampulemensis sp. n., Chimarra glaubrechti sp. n., Hellyethira lacustris sp. n., Orthotrichia litoris sp. n., Ecnomus matanensis sp. n., Paduniella celebensis sp. n., Pseudoneureclipsis sorowakensis sp. n., Setodes leucocephalus sp. n., Setodes flexus sp. n. and Setodes rinteleni sp. n. The male genitalia are illustrated and diagnostic characters are provided. Keywords Insecta, Trichoptera, taxonomy, new species, Indonesia, Sulawesi, Lake Matano. Nomenclatural Acts tampulemensis Mey, 2006 (Agapetus), spec. n. glaubrechti Mey, 2006 (Chimarra), spec. n. matanensis Mey, 2006 (Ecnomus), spec. n. lacustris Mey, 2006 (Hellyethira), spec. n. litoris Mey, 2006 (Orthotrichia), spec. n. celebensis Mey, 2006 (Paduniella), spec. n. sorowakensis Mey, 2006 (Pseudoneureclipsis), spec. n. flexus Mey, 2006 (Setodes), spec. n. leucocephalus Mey, 2006 (Setodes), spec. n. rinteleni Mey, 2006 (Setodes), spec. n.